ChemInform Abstract: Total Synthesis of (‐)‐Deguelin via an Iterative Pyran‐Ring Formation Strategy. Issue 39 (September 2015) - Lee, Seungbeom; An, Hongchan; Chang, Dong‐Jo; Jang, Jaebong; Kim, Kyeojin; Sim, Jaehoon; Lee, Jeeyeon; Suh, Young‐Ger
Abstract Enantioselective synthesis of (‐)‐deguelin is accomplished via an iterative pyran‐ring formation approach.